FETAL MUMMIFICATION IN GOAT: A CASE REPORT - Koli, A B; Ramteke, S S; Naktar, S B; Patil , A D (Animal Reproduction Update, 2023)
A three year old non-descript goat in fourth parity was presented to the Veterinary  Clinical Complexes, COVAS, Udgir with the history of straining and vaginal  discharge for last four to five hours. One live male fetus was delivered through  obstetrical maneuvers which followed the delivery of mummified fetus. The goat  was treated with fluid therapy, antibiotics, NSAID and antihistamines.
Keywords: Dystocia; Goat; Mummification